Possibilities and modes of medical rehabilitation of patients with concomitant occurence of acute coronary syndrome and acute stroke - Jovanović Aleksandar; Knežević Todor; Niković Jelena; Tešović Snežana; Pejin Radoslav; Tomić Sanja (Association of Nurses Technicians and Midwives, 2022)
Background: Being the most austere manifestation of ischaemic heart disease, acute coronary syndrome is one of the most frequent causes of urgent treatment and sudden death in both developed and developing countries as well. Acute stroke is the third cause of death in developed countries, after cardiovascular diseases and tumors, and second worldwide. Besides being a disease with high mortality, it is also a disease with a highest level of disability. Aim: To determine possibilities and modes of rehabilitation of patients with concomitant occurence of acute stroke and acute coronary syndrome. Methods: Retrospective study using hospitalized patients data. 5929 hospitalized patients treated at the Institute for cardiovascular diseases in Sremska Kamenica were analyzed from January 1st 2017 to December 31st 2019, without regarding sex and age. We entered data in created database and analyzed using descriptive statistics and chi-square test. Results: Concomitant stroke and acute coronary syndrome was found in 61 patient (1.0%). There were 32 males and 29 females. Average age was 68.82. Pneumonia occured more frequently in persons with concomitant occurrence of acute stroke and acute coronary syndrome than in persons with acute coronary syndrome without acute stroke. Regarding neurological and/or cardiological condition, only 3 patients (9.0%) were eligible for rehabilitation, and in all others it was delayed or contraindicated. Conclusion: Rehabilitation of patients with concomitant occurrence of acute coronary syndrome and acute stroke was complicated, with high risk, and required multidisciplinary approach to each patient individually.